Equilibrium unemployment and investment under product and labour market imperfections - Heikki Kauppi; Erkki Koskela; Rune Stenbacka (Bank of Finland, 2004)
The study looks at the implications of product market competition and investment for price setting, wage bargaining and thereby for equilibrium unemployment in an economy with product and labour market imperfections.We show that intensified product market competition will reduce equilibrium unemployment, whereas the effect of increased capital intensity is more complex.Higher capital intensity will decrease the equilibrium unemployment when the elasticity of substitution between capital and labour is less than one, while the reverse happens when this elasticity is higher than one, but smaller than the elasticity of substitution between products.Finally, we demonstrate how labour and product market imperfections, characterised by the wage and price setting mark-ups, affect the optimal capital stock.Our findings raise important questions for future empirical research.
URN:NBN:fi:bof-20140807265
Keywords: E22; E24; J51; L11; 330; equilibrium unemployment; product market imperfections; investment; wage bargaining